2020
DOI: 10.1101/2020.10.15.341610
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hebbian learning with elasticity explains how the spontaneous motor tempo affects music performance synchronization

Abstract: Music has a tempo (or frequency of the underlying beat) that musicians maintain throughout a performance. Musicians maintain this musical tempo on their own or paced by a metronome. Behavioral studies have found that each musician shows a spontaneous rate of movement, called spontaneous motor tempo (SMT), which can be measured when a musician spontaneously plays a simple melody. Data shows that a musician's SMT systematically influences how actions align with the musical tempo. In this study we present a model… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…Despite a focus on the natural frequency of internal oscillators in timing literature, not much attention has been given to their other primary property: flexibility (referred to as elasticity in Ref. 13 and adaptability, the compliment of stability, in Ref. 14 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite a focus on the natural frequency of internal oscillators in timing literature, not much attention has been given to their other primary property: flexibility (referred to as elasticity in Ref. 13 and adaptability, the compliment of stability, in Ref. 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our first hypothesis was that tempo-matching errors calculated across both the synchronization and continuation sections of the trial (TME all ) would have a negative slope as a function of stimulus rate (IOI), arising from fast stimuli being tapped too slow and slow stimuli being tapped too fast. The dynamical systems approach predicts reduced asynchronies between stimulus and the oscillator as the difference between the stimulus frequency and the oscillator’s natural frequency (i.e., detuning) is reduced 13 since it would require more energy to coordinate motion at other frequencies 12 . In addition, since finger tapping is rate-limited due to motor and cognitive constraints 21 , and since we anticipated that most participants’ preferred rates would fall somewhere into the middle of the range, we expected tapping errors to increase at both ends of the IOI range.…”
Section: Introductionmentioning
confidence: 99%
“…The current findings add to a growing body of work indicating that spontaneous music performance rates reflect oscillatory processes that influence auditory-motor entrainment within and between individuals (Zamm et al, 2016(Zamm et al, , 2018Scheurich et al, 2018;Palmer et al, 2019;Roman et al, 2020). Whether the spontaneous performance rates reflect intrinsic timekeeping processes or biomechanical constraints is a topic for further research.…”
Section: Discussionmentioning
confidence: 59%
“…Third, the spontaneous rates are consistent within individuals, across their limb movements and melodies ( Zamm et al, 2016 ), across time of day ( Zamm et al, 2019 ; Wright and Palmer, 2020 ). Moreover, recent computational work ( Roman et al, 2020 ) indicates that the relationship between musical partners’ spontaneous frequencies and interpersonal synchrony can be accurately predicted from a model of biological oscillator entrainment, providing further credence to an oscillator framework of musical synchrony.…”
Section: Introductionmentioning
confidence: 78%
“…Finally, our findings also extend current literature on the functional role of spontaneous rhythmic preferences. Previous work showed that spontaneous motor tempi can affect externally paced motor performance in personal (Bardy et al, 2015;McAuley et al, 2006;Roman et al, 2021;Scheurich et al, 2018) and inter-personal settings (Alderisio et al, 2017;Roman et al, 2021;Zamm et al, 2015Zamm et al, , 2016Zamm et al, , 2018. In addition, previous work investigating the neural markers of rhythm perception found that neural markers modulated by the presence of a rhythm were also linked to individuals' spontaneous rhythmic preferences (Schwartze & Kotz, 2015).…”
Section: Individual Differences In Rhythm-based Perceptual Modulationmentioning
confidence: 99%